2017
DOI: 10.1186/s40168-017-0257-7
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis and microbiome flexibility in calcifying benthic foraminifera of the Great Barrier Reef

Abstract: BackgroundSymbiosis is a phenomenon that allows organisms to colonise a wide range of environments and occupy a variety of ecological niches in marine environments. Large benthic foraminifera (LBF) are crucial marine calcifiers that rely on photo-endosymbionts for growth and calcification, yet the influence of environmental conditions in shaping their interactions with prokaryotic and eukaryotic associates is poorly known.ResultsHere, we used next-generation sequencing to identify eukaryotic photosynthesizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 56 publications
(79 reference statements)
5
50
0
Order By: Relevance
“…Morphological studies showed that while LBF commonly host a single dominant symbiont species at any given time, several other diatom species can be present at low abundances (Lee et al, ), and some flexibility in these host–symbiont associations is usually observed. However, molecular studies demonstrate that this diversity is likely to have been underestimated by morphological studies (Holzmann, Berney, & Hohenegger, ; Prazeres et al, ). Molecular studies of diatom symbionts in LBF also suggest a strong, species‐specific host–symbiont relationship (Holzmann et al, ; Schmidt et al, , ; Barnes, ; Prazeres et al, ).…”
Section: Diversity and Ecological Importance Of Algal Symbiontsmentioning
confidence: 99%
See 4 more Smart Citations
“…Morphological studies showed that while LBF commonly host a single dominant symbiont species at any given time, several other diatom species can be present at low abundances (Lee et al, ), and some flexibility in these host–symbiont associations is usually observed. However, molecular studies demonstrate that this diversity is likely to have been underestimated by morphological studies (Holzmann, Berney, & Hohenegger, ; Prazeres et al, ). Molecular studies of diatom symbionts in LBF also suggest a strong, species‐specific host–symbiont relationship (Holzmann et al, ; Schmidt et al, , ; Barnes, ; Prazeres et al, ).…”
Section: Diversity and Ecological Importance Of Algal Symbiontsmentioning
confidence: 99%
“…However, molecular studies demonstrate that this diversity is likely to have been underestimated by morphological studies (Holzmann, Berney, & Hohenegger, ; Prazeres et al, ). Molecular studies of diatom symbionts in LBF also suggest a strong, species‐specific host–symbiont relationship (Holzmann et al, ; Schmidt et al, , ; Barnes, ; Prazeres et al, ). Diatom‐bearing species also have associations with other groups of algae such as the green microalga Chlorella (Lee, ), and possibly with rhodophytes, usually at very low relative densities (Prazeres et al, ).…”
Section: Diversity and Ecological Importance Of Algal Symbiontsmentioning
confidence: 99%
See 3 more Smart Citations